2020
DOI: 10.1108/jima-12-2019-0270
|View full text |Cite
|
Sign up to set email alerts
|

Muslims and non-Muslims intention to hold Shariah-compliant credit cards: a SmartPLS approach

Abstract: Purpose The purpose of this paper is to examine the relationship between attitude, subjective norm, perceived behavioural control, religiosity, knowledge and Shariah-compliance with intention to hold Shariah-compliant credit card (SCCC) amongst Muslims and non-Muslims. Design/methodology/approach Researchers used survey questionnaire to collect data and applied a purposive sampling method, then analyzing the data using descriptive statistics and also multi-group analysis of SmartPLS. Findings For Muslims, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 95 publications
(112 reference statements)
4
31
1
1
Order By: Relevance
“…Firstly, the results of the study indicate that attitude has the strongest influence on Muslims' intention to visit homestays in Sabah. This finding supported earlier studies by Johan et al (2020), Farhat et al (2019), Bashir (2019), Memon et al (2019), Ng et al (2019), Patwary et al (2018), Suki & Salleh (2018), Elseidi (2017), Khan & Azam (2016), Amin et al (2011), Lada et al (2009), Lee & Moscardo (2005), Lam & Hsu (2004) and Chen (1998). In short, Muslims' attitude plays an important role in predicting their intention to visit homestays in Sabah.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Firstly, the results of the study indicate that attitude has the strongest influence on Muslims' intention to visit homestays in Sabah. This finding supported earlier studies by Johan et al (2020), Farhat et al (2019), Bashir (2019), Memon et al (2019), Ng et al (2019), Patwary et al (2018), Suki & Salleh (2018), Elseidi (2017), Khan & Azam (2016), Amin et al (2011), Lada et al (2009), Lee & Moscardo (2005), Lam & Hsu (2004) and Chen (1998). In short, Muslims' attitude plays an important role in predicting their intention to visit homestays in Sabah.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a distinction between the Muslims' beliefs and practices are imperative. In the Islamic marketing literature, religiosity has been posited as an essential determiner of Muslims' decision to purchase a particular product or service (Mukhtar & Butt, 2012).Thus, it is right to say that Islam religion is one of the most important determinants of Muslims' intention and attitude (Johan et al, 2020). In a more recent study, Haque et al (2019) have found that religiosity was positively affecting Muslims' purchase intention toward Shari'ah-compliant hotel in Malaysia.…”
Section: The Effect Of Religious Belief On Intentionmentioning
confidence: 99%
“…Almost all respondents believe that using Islamic FinTech will bring more blessings in running their business. This is because for them by using Islamic FinTech products and services, it means that they have tried to follow Islamic rules in gathering and trying to avoid prohibited transactions such as riba, gharar, and maysir, especially in terms of the need for venture capital, investment, and other financing schemes.These results indicate that religiosity is a shield for an individual to commit to what he believes in an act whether it is permissible or not based on what has been outlined by religion (Johan et al, 2020). In addition, religiosity is the main drivers to attract intention in case of using new or novel products (Ateeq-ur-Rehman & Shabbir, 2010;Mansori, Sambasivan, & Md-Sidin, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…Religiosity is the individual's ability to commit to religious beliefs by obeying what can and should not be done including values and practices in everyday life (Johan, Hussain, Mohd, & Kamaruddin, 2020). In contemporary life, religion basically plays a significant ethical role in which the entire life it lives is shaped by divine law in religion.…”
Section: Religiositymentioning
confidence: 99%
“…We used partial least squares (PLS)-structual equation modeling (SEM) to test our measurements and structural model, because of its superiority in a complex structural model with relatively numerous constructs for theory development and prediction purposes (Hair et al , 2014; Johan et al , 2020; Rigdon et al , 2017). To test the internal consistency, we used composite reliability and Cronbach’s alpha, whereas to test the construct’s validity (convergent and discriminant) we used average variance extracted (AVE) score, the Fornell–Larcker criterion and cross-loadings (Hair et al , 2014).…”
Section: Resultsmentioning
confidence: 99%